Athrombia Thrombocytopathica - Inceman, Seref; Uçar, Sami; Ulutin, Orhan Nuri (Thrombosis and Haemostasis, 1960)
The authors reported a primary congenital thrombocytopathy in a case of erythroblastosis foetalis born with a hemorrhagic diathesis. The case was followed from the day of birth through the 2nd year. The boy presented the picture of Willebrand-Jürgens type thrombopathy (primary thrombocytopathy) with some characteristics of this disease. The agglomeration and adhesivity of the platelets were defective. These were corrected in physiological salt solution and polyvinyl pyrolidon. Although the platelets contained the thromboplastic factor, it was not given into the media under normal conditions. The biochemical and morphological osmotic resistance revealed increased platelet resistance in hypotonic salt solutions. The increased resistance and the delay in the platelet disintegration were also observed in the study of the viscous metamorphosis by the phase contrast microscope. Consequently, in this case there was a platelet stability. The authors discussed the characteristics of this case and compared some of their findings with similar cases in the literature.